Life history, reproductive, and demographic parameters for bottlenose dolphins (Tursiops truncatus) in Sarasota Bay, Florida - Randall S. Wells; Aleta A. Hohn; Michael D. Scott; Jay C. Sweeney; Forrest I. Townsend; Jason B. Allen; Aaron A. Barleycorn; Katherine A. McHugh; Kim Bassos-Hull; Gretchen N. Lovewell; Deborah A. Duffield; Cynthia R. Smith; et al. (Frontiers in Marine Science, 2025)
Studies of the resident community of bottlenose dolphins ( Tursiops truncatus ) of Sarasota Bay, Florida, have been conducted for more than 50 years. Detailed histories have been collected for resident individuals through integrated observations, systematic photographic identification surveys, tagging and tracking, catch-and-release health assessments, remote biopsy sampling, and stranding response. This has produced a unique dataset documenting life history milestones and vital rates of a small cetacean. Analyses of data from 482 resident Sarasota Bay dolphins have revealed estimated maximum life spans of 67 years for females and 52 years for males. For females, predicted age at sexual maturation is 8.5 years, with a predicted age at first reproduction of 9.6 years. Females were observed to give birth when 6-48 years of age, and have been documented with as many as 12 calves, with 45% observed post-separation. Ten percent of females were considered to be reproductively senescent, having gone >13 years without producing a calf. For males, predicted age at sexual maturation is 10 years. Males 10-43 years old sired calves, producing up to 7 calves each. The average calving interval was 3.5 years, albeit with effects due to mother’s age, birth order, and calf survival. Seasonal reproduction was evident, with 81% of births occurring during May-July. Mean annual birth rate was 0.071. Mean annual fecundity was 0.182 births/adult female (defined as females 6 yrs or older). Recruitment rate through reproduction was estimated to be 0.050 based on calves surviving their first year. Immigration was infrequent, with an estimated annual rate of 0.003-0.013. Estimated mean annual maximum loss rate, from mortality, emigration, and changed identification characteristics, was 0.072. Periods of increased loss rates were related to environmental events, and factors that may be important to long-term population resilience were suggested.

Prey-Related Asphyxiation in Harbor Porpoises (Phocoena phocoena) along the U.S. West Coast: Importance of American Shad (Alosa sapidissima) on Adult Female Harbor Porpoise Mortality - Cindy R. Elliser; John Calambokidis; Dalin N. D’Alessandro; Deborah A. Duffield; Jessica L. Huggins; James Rice; Isidore Szczepaniak; Marc Webber (Oceans, 2020)
Harbor porpoise (Phocoena phocoena) diets are predominantly comprised of small fish species (<30 cm) and squid. However, predation on larger species (up to 63 cm) occurs, raising the question of increased risk of asphyxiation associated with this behavior. Literature was reviewed and stranding data from 1983 to 2020 from the U.S. West Coast (including California, Oregon and Washington) were searched for cases of prey-related asphyxiation of harbor porpoises and analyzed in relation to age, sex, reproductive status and prey species. Twenty-nine cases were documented. Twenty-seven cases involved large prey; non-native American shad caused the asphyxiation in 87% of the cases where the prey species was identified. The majority (92%) of harbor porpoises were females, and at least 83.3% were pregnant or recently post-partum. Reproductively active females may be more likely to attempt potentially risky behavior in order to compensate for their increased energetic needs. Increasing numbers of non-native American shad may pose a unique danger in this region for harbor porpoises not adapted to deal with the challenges of that prey. This may be a cause for concern, as there is likely an interaction between location, age and reproductive status on the diet composition and foraging strategies of harbor porpoises.

Ancient DNA reveals genotypic relationships among Oregon populations of the sea otter (Enhydra lutris) - Kim Valentine; Deborah A. Duffield; Lorelei E. Patrick; David R. Hatch; Virginia L. Butler; Roberta L. Hall; Niles Lehman (Conservation Genetics, 2008)

Surfactant Enhanced Mobilization of Mineral Oil within Porous Media - A. R. Duffield; R. S. Ramamurthy; J. R. Campanelli (Water, Air, & Soil Pollution, 2003)